Calorimetric studies of crystallization in Se76Te20Sn2Ge2 glass under heating/cooling mode. (1st January 2023) - Pal, Shiv Kumar; Sharma, Dipti; Mehta, Neeraj
Abstract: In the liquid-solid phase transition analysis, it was observed that two phenomena namely crystallization and glass transition take place, whenever we cool a liquid or melt a solid. In the present endeavor, we have tried to analyze the comparative study of crystallization kinetics using comprehensive iso-conversional methods in both heating/cooling modes of quaternary Se76 Te20 Sn2 Ge2 glassy material synthesized by a very simple and famous melt quenching technique. Differential Scanning Calorimetry (DSC) was employed for this analysis. The effect of heating, as well as cooling rates on the crystallization kinetics, was investigated. Various kinetic parameters like activation energy using the iso-conversional approach, the reaction rate constant, the Avrami index, Meyer-Neldel energy, etc have been calculated for both heating and cooling modes.